Finite element analysis of the static behavior of steel frames with combined precast reinforced concrete infill wall structures - MU Zai-gen; YANG Yu-qing; FENG Lei; WANG Zhe (工程科学学报, 2017)
Steel frames with precast reinforced concrete infill walls are a new type of composite structures. These composite structures have excellent lateral resistance behavior because of double defense lines comprising the steel frame and infill walls. At the same time, precast members and prefabricated buildings are favorable for the development of the housing industry. Considering the difficulties in the transportation and installation of large precast RC infill walls, steel frames with vertical and horizontal combined precast RC infill wall structures were proposed, and finite element models were established by using ABAQUS to analyze the mechanical behaviors of the structures. By analyzing load-displacement curves, stress distributions, and deformations of members, the damage characteristics, and mechanical behaviors of the structure were studied. The results show that the whole bolt structure has good bearing capacity and ductility owing to its reasonable load transfer path; the vertical combined model has excellent initial stiffness and ultimate bearing capacity, similar to the whole bolt connection precast RC wall. Furthermore, the vertical combined precast RC infill wall is convenient for transportation and installation. However, the initial stiffness and ultimate bearing capacity of the horizontal combined model are both less than the corresponding values for the whole bolt model and the vertical combined model because of the lack of an effective load transfer path between the top and bottom RC walls. Hence, this horizontal model is not favorable for practical engineering applications.